Etika Profesi dan Tanggung Jawab Guru di Era Digital terhadap Kualitas Interaksi Pembelajaran di SMA - Helmy Nabil Fawwazi; Feby Khoirinnisa Wahidah; Zuhrifa Putri Sulistyo; Nur Khasanah (CAHAYA: Journal of Research on Science Education, 2026)
This study discusses the role of professional ethics and teacher responsibility in the digital era toward the quality of learning interactions in senior high schools (SMA). The development of digital technology has changed learning patterns and created new challenges related to professionalism, communication ethics, and the use of technology in education. Teachers are required not only to master technology, but also to apply ethical values and professional responsibility in the learning process. This study uses a qualitative approach through library research by analyzing journals, books, and scientific articles related to teacher professional ethics, digital learning, and learning interaction quality. The results show that professional ethics and teacher responsibility have an important influence on the quality of digital learning interactions. Teachers who have good ethical awareness and digital literacy are able to create communicative, interactive, and meaningful learning processes. In addition, the use of technology that is balanced with ethical values can improve professionalism, student participation, and the effectiveness of learning interactions in SMA.